Waiting in the Pampas: The Enduring Popularity of Beckett’s Plays in Argentina - Pratt, Cathal Patrick (ABEI Journal, 2014)
This paper’s objective is to address the popularity of Samuel Beckett’s dramatic oeuvre in Argentina. While Waiting for Godot and otherplays have found homes in many assorted cultures and countries, Argentina is particularly suited to several different readings of the text. Given the frequency of urban and rural productions of the plays, including Buenos Aires’s Festival Beckett, the paper argues that these works have resonance with this particular region. Of key interest is the relationship between avant-garde theatre and the Argentine dramatic subgenre el grotesco criollo. Rising to prominence during the Dirty War and military junta era, the subgenre is became a way to resist government censorship. By placing acts of interrogation and torture on the stage, Argentine playwrights like Griselda Gambaro expressed that which could not be said officially. This drive to show the unshowable and fixation on hierarchies of power prepare the theatre-going public for the mid-1980’s when Beckett’s plays are no longer banned. Furthermore, outside of Buenos Aires, plays like Waiting for Godot are known to be staged in the western Pampas--a largely rural and isolated region. The nature of power relationships here lendsitself easily to interpreting the work in a post-colonial light. It may be that the popularity of Beckett’s work stems from the same pressures that served as the impetus for Beckett’s attack on the word surface. If Beckett is writing, as Eagleton suggests, in response to the horrors of WWII, then perhaps Argentine theatre maintains examples of convergent evolution in literature from the Dirty War period.Keywords: Beckett; Waiting for Godot.